Experimental verification of cylindrical air-breathing continuous rotating detonation engine fueled by non-premixed ethylene. (December 2021) - Wang, Guangyu; Liu, Weidong; Liu, Shijie; Zhang, Hailong; Peng, Haoyang; Zhou, Yunfan
Abstract: An especial air-breathing continuous rotating detonation engine without a centerbody is proposed to reduce energy loss and simplify the structure, which is analogous to a typical scramjet combustor with the cavity. Non-premixed ethylene/air rotating detonation experiments are performed in a direct-connect experimental facility with an air inflow of 860 K total temperature (Ma 2.02). Two combustion modes (continuous rotating detonation and deflagration mode) are discovered with varying equivalent ratio (ER). A proper accumulation layer of the combustible mixture in the cavity re-circulation region attaching the outer wall is critical for rotating detonation realization. The average propagation velocity of the detonation wave is 1297.1 m/s (78.5% C-J velocity) at ER = 0.64 with the combustor pressure of 230 kPa. Its motion of the reaction zone is quantitatively verified to be rotating through the integral of chemiluminescence intensity. Besides, it is confirmed by the optical observation that deflagration could also self-sustain in the short combustor with the axial-moving flame. The combustor pressure of deflagration mode can reach 220 kPa with ER = 0.56. Though the combustor pressure of detonation is slightly higher than that of deflagration, the impact of combustor high-pressure on the inflow of detonation mode is much stronger through the induced oblique shock wave. Highlights: An air-breathing CRD engine with cylindrical isolator and combustor is proposed. Non-premixed ethylene-air CRD is realize d in the cylindrical isolator and combustor. ER significantly affects the combustion mode with the extremely low rich limit. Deflagration can maintain in such a short combustor (150 mm) in supersonic inflow. The impact of CRD on the inflow is mainly through the upstream oblique shock wave.